Restroom Hygiene Smart Monitoring System Incorporating Lora Technology - Azman F.I.; Saleh N.L.; Ali A.M.; Sali A.; Noor A.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Internet of things; Low power electronics; Cloud servers; Consumption; Hygiene; IoT; Lora; Low Power; Networking protocols; Radio modulation; Smart monitoring systems; Wide-area networks; Wide area networks